Advances in Fire and Process Safety Select Proceedings of HSFEA 2016 (Springer Transactions in Civil and Environmental Engineering,, 2018)
This book presents the proceedings of the International Conference on Health, Safety, Fire, Environment, and Allied Sciences (HSFEA 2016). The book highlights the latest developments in the field of science and technology aimed at improving health and safety in the workplace. The volume comprises content from leading scientists, engineers, and policy makers. The papers included in this volume look at identifying the limitations of the existing approaches and open new avenues for future research. The book also looks at the accident and work-health records, specifically in Asian countries, and discusses measures to improve the Asian standards and implementation issues with regards to workplace health and safety. The contents of this volume will be of interest to researchers, practitioners, and policy makers alike. .